(untitled) (Revista Electrónica REDINE, 2019)
The main objective of this project was to propose a comprehensive quality management plan for the improvement of the patient admission process at the Dr. Pastor Oropeza Social Security Hospital. From Barquisimeto, Lara state. The study was developed as a descriptive investigation, based on the positivist paradigm and supported by a field work; Eighty-three (83) subjects, twenty-five (25) of the department staff and fifty-eight (58) patients were taken as population. The interview and the survey were applied as data collection techniques, through a (01) interview script to the board and (01) questionnaire to the staff. Its reliability was through the Cronbach Alpha coefficient. It was concluded that there is a poor tendency in tangible elements; since the company has few teams capable of providing good service to patients. The physical facilities of the Dr. Pastor Oropeza Social Security Hospital are not visually attractive, in the same way it was determined that the staff does not have a commitment and attitude when it comes to caring for patients. A proposal was generated where the Malcom Baldrige Model is presented to improve the quality of the service and increase the productivity of the Institution.